1989
DOI: 10.3109/02841868909092288
|View full text |Cite
|
Sign up to set email alerts
|

Ca 125 Assay Used in Conjunction with Ca 15–3 and Tag-72 Assays for Discrimination Between Malignant and Non-Malignant Diseases of the Ovary

Abstract: It has previously been suggested by the authors that elevated serum CA 125 levels may be of value in discriminating malignant from non-malignant pathologies among women with pelvic masses. Enhancement of this discrimination capacity might be achieved by utilizing additional serum assays. To test this hypothesis CA 125, CA 15-3 and TAG-72 levels were determined in double-blind fashion on 219 sera from patients undergoing diagnostic laparotomy for pelvic masses at six gynecological departments in the Stockholm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

1991
1991
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 4 publications
2
13
0
2
Order By: Relevance
“…Extremely high specificity (98.9 %) was achieved when a positive result was defined as a CA125 level greater than 30 U/ml in combination with either a CA15.3 greater than 30 U/ml or a TAG 72.3 greater than 10 U/ml (Jacobs et al 1993b). These findings were confirmed by other workers (Einhorn et al 1989) who found the specificity for malignancy to be 98 % when all three antigens were elevated, compared with 83 % for CA125 used as a single test. However, by adding the two tests the sensitivity to discriminate malignant from benign diseases decreased to 69%.…”
Section: Other Tumour Markerssupporting
confidence: 79%
“…Extremely high specificity (98.9 %) was achieved when a positive result was defined as a CA125 level greater than 30 U/ml in combination with either a CA15.3 greater than 30 U/ml or a TAG 72.3 greater than 10 U/ml (Jacobs et al 1993b). These findings were confirmed by other workers (Einhorn et al 1989) who found the specificity for malignancy to be 98 % when all three antigens were elevated, compared with 83 % for CA125 used as a single test. However, by adding the two tests the sensitivity to discriminate malignant from benign diseases decreased to 69%.…”
Section: Other Tumour Markerssupporting
confidence: 79%
“…Einhorn et al evaluated CA125 concentrations together with those of CA15-3 and TAG-72 in 219 patients undergoing diagnostic laparotomy for pelvic masses. They found that the three tumor markers increased the specificity for detecting ovarian cancer but reduced the sensitivity of the CA125 assay [10]. Similar observations were made by Soper et al, who showed that by combining CA15-3 and TAG-72 measurements with CA125, the specificity for detecting ovarian cancer rose from 83% to 98%, but the sensitivity was reduced from 88% to 73% [11].…”
Section: Screening and Diagnosissupporting
confidence: 64%
“…We and others found that the commonly used tumor marker CA-125 was elevated (>35,000 units/L) in 82% of the ovarian cancer patients (2). However, as has been shown by many previously, CA-125 was also elevated in part of the patients with benign tumors and, therefore, lacks sufficient sensitivity and specificity to be used solitarily for distinguishing between malignant and benign pelvic mass (11). To our knowledge, IL-7 has never been investigated for use as a diagnostic tool in ovarian cancer.…”
Section: Discussionmentioning
confidence: 80%